This problem look intimidating but if we can rewrite it using logarithm properties, it actually really easy.
*Remember: color(red)(log(a/b) hArr loga- log b ; color(blue)(loga^n = n log a ; color(green)(ln e= 1)
Step 1: Rewrite the logarithm expression
f(x)= ln((e^(x^2+1))/(2x^3-1)^(1/2)) hArr color(red)(f(x)= ln(e^(x^2+1))-ln(2x^3-1)^(1/2)
hArr f(x)= color(blue)((x^2 +1)*(ln e))-1/2ln (2x^3-1)
hArr f(x)=color(green)( (x^2 +1)) -1/2 ln(2x^3 -1)
==========================================
Step 2: Now can can begin to differentiate the function
*Remember color(red)(g(x)= lnx ; g'(x)= (dx)/x)
f'(x)= color(green)(2x) -1/2((color(red)(6x^2))/(2x^3-1)) Differentiate
f'(x)= color(green)(2x) -((color(red)(3x^2))/(2x^3-1)) Simplify
f'(x)= (color(green)(2x)color(red)( (2x^3 -1)) -3x^2)/(2x^3 -1) Common denominator
f'(x)= (4x^4 -2x-3x^2)/(2x^3 -1) Distributen and simplify
f'(x)= (x(4x^3 -3x-2))/(2x^3 -1) Better answer :)